2020
DOI: 10.4085/1062-6050-482-18
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Ultrasound-Based Muscle Size and Mechanical Properties of the Cervical-Flexor and -Extensor Muscles

Abstract: Context Neck pain (NP), neck injuries, and concussions are more prevalent in female athletes than in their male counterparts. Females exhibit less neck girth, strength, and stiffness against a perturbation. As part of the clinical examination for individuals with NP, ultrasound (US)–based imaging of the cervical muscles has become common. Muscle size or thickness and stiffness can be measured with US-based B-mode and shear-wave elastography (SWE), respectively. Information on reliability, nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 31 publications
2
20
0
Order By: Relevance
“…Myoglobin also absorbs infrared light (Bashkatov et al, 2011 ; Jacques, 2013 ) so the sternocleidomastoid muscle could confound the relationship between absorption signals and IJV blood volume in addition to the effects of hemoglobin. We observed the sternocleidomastoid to be significantly thicker in men compared to women, consistent with previous findings (Nagai et al, 2020 ), and weakly correlated with JVA signal. Importantly, however, while myoglobin within muscle overlying the IJV might contribute to the larger baseline JVA signal in men, it would not account for the greater change in JVA with HDT or LBNP.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Myoglobin also absorbs infrared light (Bashkatov et al, 2011 ; Jacques, 2013 ) so the sternocleidomastoid muscle could confound the relationship between absorption signals and IJV blood volume in addition to the effects of hemoglobin. We observed the sternocleidomastoid to be significantly thicker in men compared to women, consistent with previous findings (Nagai et al, 2020 ), and weakly correlated with JVA signal. Importantly, however, while myoglobin within muscle overlying the IJV might contribute to the larger baseline JVA signal in men, it would not account for the greater change in JVA with HDT or LBNP.…”
Section: Discussionsupporting
confidence: 93%
“…Sex‐based differences in CSA are equivocal (Jeon et al, 2020 ; Magnano et al, 2016 ), although there is some indication that men have larger right IJV than women (Magnano et al, 2016 ), while IJV distensibility appears similar between men and women (Mortensen et al, 1990 ). In contrast, hemoglobin concentrations (Murphy, 2014 ) and sternocleidomastoid muscle volume (Nagai et al, 2020 ) are known to be greater in men. These differences, as well as possible sex differences in CSA, may confound the utility of CHI to monitor IJV blood volume between sexes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In sex differences, some previous studies demonstrated that there was a sex difference in muscle stiffness based on ultrasound shear wave elastography, and that males generally had higher muscle stiffness than females [ 30 , 31 , 32 ]. However, the sex differences in muscle stiffness have not been previously evaluated for paraspinal and psoas muscles using the MRE technique.…”
Section: Discussionmentioning
confidence: 99%
“…In the young group, the shear elastic modulus of the multifidus muscles at T13 was lower than that at L3. Although the muscle length and CSA of the multifidus muscle were significantly different between T13 and L3, studies in humans showed no significant correlations between muscle mass and muscle stiffness [ 33 40 41 ]. In this study, the elastic shear modulus of the multifidus muscle also showed no change in relation to changes in muscle length or CSA of the multifidus muscle in the adult group.…”
Section: Discussionmentioning
confidence: 99%